PENGARUH SERVICE CONVENIENCE DAN LIFESTYLE TERHADAP IMPULSE BUYING MELALUI ELECTRONIC WORD OF MOUTH - Faishal Aulia Zahran, - (2022)
Impulse buying has become a part of today's society, supported by increasingly advanced information technology and the ongoing COVID-19 situation. The change in one's shopping style from offline to online makes a person's impulsive power increase. The phenomenon of planned purchases is one of the ways to develop the market. Convenience of services and recommendations is one of the external factors that causes someone to make an impulse purchase. Meanwhile, internally, a person's lifestyle is the reason someone buys things impulsively. Tokopedia will become one of the best e-commerce platforms during 2022 due to the high visiting power of the public, this may lead to impulse buying. This study was conducted on 121 respondents using the Tokopedia application which aims to find the effect of service convenience and lifestyle on impulse buying through electronic word of mouth. The results of this study are the significant influence of service convenience and lifestyle on electronic word of mouth. Variable service convenience, lifestyle and electronic word of mouth on impulse have a significant influence. Variable electronic word of mouth does not mediate between service convenience and impulse buying, but lifestyle and impulse buying can be mediated by electronic word of mouth.